Effects of various packet scheduling algorithms on the performance of high speed downlink shared channel in a WCDMA network - Ong, Choon Jin. (2008)
In this dissertation, the High Speed Downlink Shared Channel (HS-DSCH) is considered for the offering of web-browsing services and the effects of using different packet schedulers in a WCDMA system using HSDPA are evaluated.